Measurement of the thermal diffusivity of materials by diverging thermal wave technique - Abd. Moksin, Mohd Maarof; Mat Yunus, Wan Mahmood; Talib, Zainal Abidin (Universiti Pertanian Malaysia Press, 1994)
The applications of diverging thermal wave technique to measure thermal diffusivities of materials are reported. In essence, the technique makes use of the information content of the thermal waves observed by means of a wide band infrared detector, that laterally displaced from the heat source, following pulsed laser excitation of the materials. Some observations obtained from aluminium, lead, graphite foil, and zirconium graphite samples are presented.